Aus der Geschichte der entomologischen Sammlungen des ehemaligen Deutschen Entomologischen Instituts. I. Allgemeiner Teil. - II. Die Dipterensammlung. - Rohlfien, Klaus (Contributions to Entomology = Beiträge zur Entomologie, 1975)
The present paper is the first of a series describing the history of the entomological collections of the former Deutsches Entomologisches Institut, now the Department of Taxonomy of Insects of the Institute of Plant Protection Research. A general survey of the development of the collections is followed by a special part dealing with the collection of Diptera. Its development, its important parts, the various modes of acquisition, its curators, the most important determiners, its present state and structure and the future work with it are discussed.